Safeguarding Nepal’s Paddy Farmers: Necessity, Challenges, and Policy Directions for Crop Insurance - Ghimire, Shiva Sundar; Shrestha, Shiddi Ganesh; Dahal, Kishor Chandra; Sharma, Govindra Prasad; Sigdel, Udit Prakash (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This study aims to identify and analyze challenges of the adoption of paddy crop insurance in the terai regions, focusing on farmers’ perceptions, institutional efficiency, and gaps in policy implementation. Design/methodology/approach: The cluster-based random sampling was used to collect data from 460 respondents, divided into insured and non-insured groups from paddy-growing farmers from Chitwan and Bardiya districts. Findings: Major constraints include limited awareness, negative perceptions, delayed claim settlements, and weak institutional coordination. The non-insured farmers highlighted poor understanding of the policy, perceived low payouts, financial limitations, and inadequate support from financial institutions as key obstacles. Conclusion: The findings revealed that strengthening awareness campaigns, ensuring timely and transparent claim processing, and linking insurance with credit and subsidy programs are vital policy measures to increase adoption and enhance resilience in Nepal’s rice sector . Implications: This study provides suggestions to policymakers, regulatory institutions, and insurers to design and execute the paddy crop insurance program by addressing its actual challenges faced by farmers. Originality/value: This study provides a novel perspective by incorporating the field situation, examination of existing policies, and stakeholders’ institutional views. JEL Classification: Q14, Q12, G22, Q18